2006
DOI: 10.1590/s0036-46652006000500001
|View full text |Cite
|
Sign up to set email alerts
|

PCR-based identification of Burkholderia pseudomallei

Abstract: SUMMARYDNA amplification techniques are being used increasingly in clinical laboratories to confirm the identity of medically important bacteria. A PCR-based identification method has been in use in our centre for 10 years for Burkholderia pseudomallei and was used to confirm the identity of bacteria isolated from cases of melioidosis in Ceará since 2003. This particular method has been used as a reference standard for less discriminatory methods. In this study we evaluated three PCR-based methods of B. pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 18 publications
0
57
0
1
Order By: Relevance
“…27 In time, a PCR assay was developed for B. pseudomallei identification based on a gene sequence associated with a bacterial fatty acid specific to B. pseudomallei . 28,29 This assay was more reliable than the earlier PCR assay used in WA during the first one-half of the decade. Another improvement was sequencing of a PCR-amplified RecA gene product.…”
mentioning
confidence: 87%
“…27 In time, a PCR assay was developed for B. pseudomallei identification based on a gene sequence associated with a bacterial fatty acid specific to B. pseudomallei . 28,29 This assay was more reliable than the earlier PCR assay used in WA during the first one-half of the decade. Another improvement was sequencing of a PCR-amplified RecA gene product.…”
mentioning
confidence: 87%
“…Confirmed B. pseudomallei were then transferred to Perth, Western Australia for detailed characterization. Isolates were sent as suspensions of bacteria in sterile water and duplicated in nutrient agar-embedded bacteriology [13][14][15] Confirmed B. pseudomallei were also subjected to biogeographic attribution PCR assays for Yersinia-like fimbrial (YLF) and Burkholderia thailandensis-like flagellum and chemotaxis (BTFC) gene clusters. 16 Molecular epidemiology.…”
Section: Methodsmentioning
confidence: 99%
“…When specific assays are conducted in an effort to diagnose glanders, serology may be complicated by cross-reactivity between B. mallei and B. pseudomallei antisera. Although PCR assays for B. mallei have been available since the late 1990s, a search of the medical literature reveals no documentation of their use in a comparative study (Brook et al, 1997;Merritt et al, 2006). In the study reported here, PCR, culture and histopathology were compared for diagnostic applicability.…”
Section: Introductionmentioning
confidence: 99%